2014
DOI: 10.1002/anie.201408399
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Controlled Synthesis of Platinum–Copper Hierarchical Trigonal Bipyramid Nanoframes

Abstract: Mastery over the structure of materials at nanoscale can effectively tailor and control their catalytic properties, enabling enhancement in both activity and durability. We report a size-controlled synthesis of novel Pt-Cu hierarchical trigonal bipyramid nanoframes (HTBNFs). The obtained nanocrystals looked like a trigonal bipyramid on the whole, composed of similar ordered frame structural units. By varying the amount of KI involved in the reaction, HTBNFs with variable sizes from 110 to 250 nm could be obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 51 publications
5
98
0
Order By: Relevance
“…When the amount of NaI was 15 mg, hollow polyhedrons were prepared (Figure S10b, Supporting Information), indicating that NaI is the necessary factor to form hollow structure. As previously reported, the strong coordination interaction between I − and Pt 4+ could lead to the preferential reduction of Cu 2+ , and thus Pt precursor could replace Cu atoms to form the hollow structure. As the amount of NaI further increased, the structure of products could not be controlled precisely (Figure S10c, Supporting Information).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…When the amount of NaI was 15 mg, hollow polyhedrons were prepared (Figure S10b, Supporting Information), indicating that NaI is the necessary factor to form hollow structure. As previously reported, the strong coordination interaction between I − and Pt 4+ could lead to the preferential reduction of Cu 2+ , and thus Pt precursor could replace Cu atoms to form the hollow structure. As the amount of NaI further increased, the structure of products could not be controlled precisely (Figure S10c, Supporting Information).…”
Section: Resultssupporting
confidence: 60%
“…In this work, a series of control experiments was carried out to investigate the influences of reducing and stabilizing agents on reduction kinetics and structure for Pt–Cu–Mn UNFs. It was found that metal precursors have obvious interactions with threonine, NaI, and ethanolamine (see details in Figures S6–S8, Supporting Information), indicating that threonine, NaI, and ethanolamine all play significant roles in controlling the reduction kinetics and affecting the structure . To gain insight into the influence on structure, TEM was employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D and E): Reproduced with permission from Refs. , , respectively. F and G): Reproduced with permission from Ref.…”
Section: Electrocatalytic Applications Of Pt‐based Bimetallic Alloy Nmentioning
confidence: 98%
“…Consequently, CTAB was proposed to promote the formation of Cu nanocrystals, and the subsequent galvanic replacement between preformed Cu nanocrystals with Pt species in the solution finally leads to PtCu 3 hollow nanocages. Another type of hollow PtCu nanoparticles, PtCu hierarchical trigonal bipyramid nanoframes (Figure D), has been generated by heating a mixed solution of aqueous, ethylene glycol (EG), CuCl 2 , H 2 PtCl 6 , KI, and PVP at 225 °C for 0.5 h . The obtained nanocrystals looked like a trigonal bipyramid as a whole and were composed of a series of similar frame structural units with sub‐5 nm branched tips.…”
Section: Controllable Synthesis Of Pt‐based Bimetallic Alloy Nanostrumentioning
confidence: 99%